2018
DOI: 10.18203/2349-2902.isj20181103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of cholecystectomy on common bile duct diameter using ultrasonography and liver function test: a prospective study

Abstract: INTRODUCTIONThe evolution of the common bile duct diameter following cholecystectomy has been a matter of considerable scientific debate in the surgical, radiological and sonographic literature for several decades. Many of the scientist, who worked on this subject initially did not find any considerable changes in the CBD diameter after cholecystectomy. Different factors influencing the post cholecystectomy CBD diameter have been implicated. Ultrasound has emerged as a diagnostic imaging method of choice for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, no previous study has analyzed serial follow-up examinations to investigate long-term changes in the CBD diameter. Most previous studies had a short follow-up period of approximately one year ( 14 15 16 17 18 19 ) and therefore, could not determine whether CBD continued to increase even after that. Although only 17 patients had a long-term follow-up period of 2–10 years, most patients showed a tendency for CBD to increase during the first 1–2 years after cholecystectomy and did not change significantly thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, no previous study has analyzed serial follow-up examinations to investigate long-term changes in the CBD diameter. Most previous studies had a short follow-up period of approximately one year ( 14 15 16 17 18 19 ) and therefore, could not determine whether CBD continued to increase even after that. Although only 17 patients had a long-term follow-up period of 2–10 years, most patients showed a tendency for CBD to increase during the first 1–2 years after cholecystectomy and did not change significantly thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…However, unless a biliary obstruction is clinically suspected, these additional tests rarely yield positive findings ( 5 ). This is because CBD dilatation is commonly non-obstructive, with the two most common etiologies being senile changes ( 8 9 10 11 ) and compensatory dilatation after cholecystectomy ( 12 13 14 15 16 17 18 19 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahour et al 9 noted its prevalence in dogs in 1968. Graham et al 10 released an ultrasonographic research of 67 asymptomatic patients more recently, and 56 (84%) of these patients demonstrated normal duct size following cholecystectomy. They also came to the conclusion that channel dilatation following cholecystectomy was uncommon.…”
Section: Discussionmentioning
confidence: 99%